IMPLEMENTASI NILAI BUDAYA LOKAL SASAK DALAM PENDIDIKAN KARAKTER SEBAGAI UPAYA PENGUATAN SIKAP SOSIAL SISWA DI SD ‘AISYIYAH 1 MATARAM - Mardiyah Hayati; Niswatun Hasanah; Yuliananingsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the implementation of Sasak local cultural values in character education as a strategy to strengthen students’ social attitudes at SD ‘Aisyiyah 1 Mataram. The research used a qualitative descriptive approach. Data were collected through participatory observation, in-depth interviews with teachers and the principal, and documentation of learning activities. The results revealed that local cultural values such as mutual cooperation, politeness, and responsibility were integrated into teaching-learning activities, religious practices, and daily habits at school. This integration effectively fostered positive social behaviors among students, including respect, environmental awareness, and cooperation. Implementing character education based on Sasak local culture proved to be an effective strategy to reinforce students’ cultural identity and social attitudes in the primary school context.